Digitalisation and its impact on SME finance in Sub-Saharan Africa: Reviewing the hype and actual developments - Sabrina Disse; Christoph Sommer (Deutsches Institut für Entwicklungspolitik (DIE), 2020)
Small and medium-sized enterprises (SMEs) are pivotal for inclusive economic development, but suffer disproportionally from institutional and market failures, especially from constrained access to external finance. Digitalisation of the financial industry is often seen as a game changer. This paper aims to answer the question what the role is of digital financial instruments in SME finance in Sub-Saharan Africa (SSA). It discusses the opportunities and challenges of digital advances for SME finance in general and of three specific financing instruments in Sub-Saharan Africa, namely mobile money (including digital credits), crowdfunding (including peer-to-peer lending) and public equity, in order to contrast the hype around digital finance with actual market developments and trends. Over 90 per cent of firms are small and medium-sized enterprises employing more than half of the formal workforce worldwide and more than 60 per cent in low- and middle-income countries (LMICs). SMEs also account for most of the new jobs created (or at least as much as larger firms). They create economic opportunities such as employment, skill development and upward mobility in diverse geographic areas and economic sectors, and provide a livelihood and income for diverse segments of the labour force, including low-skilled workers as well as disadvantaged and marginalised groups such as young people, women and minorities. Hence, SMEs can foster inclusive economic development and subsequently contribute to social cohesion. A substantial share of national value added is attributed to SMEs and the SME segment is strongly and positively associated with economic growth (even though no causality can be claimed in this respect) and economic diversification. SMEs are also vital for advances in productivity and innovation, as small and young firms may introduce new, efficient technologies or - especially important for LMICs -make small modifications in order to adapt innovations to the local or national contexts or benefit from knowledge spillover. In short, SMEs play a crucial role for economic development. (...)
Keywords: 330